As marcas da cidade: a dinâmica da pixação em São Paulo The city's marks: the taggers dynamics in São Paulo - Alexandre Barbosa Pereira (Lua Nova: Revista de Cultura e Política, 2010)
O artigo tem como foco os pixadores na cidade de São Paulo. Trata-se de jovens que percorrem as ruas da cidade deixando inscrita em muros, prédios e viadutos a sua marca. Tal prática, porém, não é vista com bons olhos pela população paulistana, que vê na pixação uma forma de degradação da paisagem urbana. Aborda também o modo particular com que estes jovens se apropriam do espaço urbano pelo estabelecimento de pontos de encontro, os seus points. Os pixadores têm uma maneira de conceber o centro e a periferia de São Paulo que dialoga com a dinâmica da metrópole. Embora se identifiquem com a periferia de onde são oriundos, eles têm o centro como importante local de atuação. A pesquisa revelou como eles estabelecem relações de troca, aliança e conflito entre si na cidade. The article has as focus the taggers in the city of São Paulo, who covers the streets of the city to leave written in walls, buildings and viaducts their marks. Such practice, however, is not seen with good eyes by the paulistana population who sees in this writing a degradation of the urban landscape. The article also approaches the particular way by which these young appropriate themselves of the urban space through the establishment of meeting points. The taggers have a way to conceive the center and the periphery of São Paulo that dialogues with the dynamics of the metropolis. Although they are identified with the periphery where they are from, they have the center as an important performance place. The research disclosed how they establish exchange relations, alliances and conflicts between them in the city.